Violence against women inflicted by other partner and its relationship with the mental health of adolescents in Peru - Vargas-Murga, Horacio Benjamín (2023)
Objective: Identify the relationship between physical, psychological, sexual or abandonment violence against women (the mother) inflicted by an intimate partner and the mental health that their adolescent child may suffer in Peru. Methods: Analysis of a subset of the sample of the database of epidemiological studies in mental health conducted from 2003 to 2012 by the National Institute of Mental Health “Honorio Delgado-Hideyo Noguchi” (bases corresponding to married women and their adolescent children were used, matching the data of both populations). Bivariate and multivariate analysis were performed, using the complex samples option and the use of expansion factors according to the sample design of the study. Results: Adolescents whose mothers had been victims of violence by their partner had lower scores on the scales of quality of life, personal satisfaction, self-esteem, satisfaction with life, self-efficacy and resilience and higher prevalence of suicidal behaviors, depressive episodes and social phobia, according to the bivariate and multivariate analysis performed (according to adjusted ORs), the adolescents of the coast and the urban area being more affected. Conclusions: Violence against women inflicted by an intimate partner would have an impact that goes beyond the battered woman, which transcends her family environment as a whole (especially on the mental health of her adolescent children) and therefore it would suggest a generational effect.